2021
DOI: 10.1021/acs.jpclett.1c03073
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Raman Spectroscopy of Polaron Formation in a Polymer Photocatalyst

Abstract: Polymer photocatalysts are a synthetically diverse class of materials that can be used for the production of solar fuels such as H 2 , but the underlying mechanisms by which they operate are poorly understood. Time-resolved vibrational spectroscopy provides a powerful structure-specific probe of photogenerated species. Here we report the use of time-resolved resonance Raman (TR 3 ) spectroscopy to study the formation of polaron pairs and electron polarons in one of the most active linear polymer photocatalysts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The species associated spectra (SAS) generated in the global fitting procedure for P10 and P10‐IrO 2 are shown in Figure 5c, d. Species 0 and 1 both have characteristic features of the singlet excitonic state. Given this observation, along with the identical time that species 1 takes to form in the presence and absence of IrO 2 , it can be assigned to a singlet excitonic state, which likely forms following vibrational relaxation of the initially formed hot state (species 0) in‐line with a recent time‐resolved Raman study of P10 which showed vibrational cooling occurs within 10 ps and that polaron formation can occur from both the vibrationally hot and thermalized exciton [53] . The SAS of species 2 (P10) has a maximum at ca.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The species associated spectra (SAS) generated in the global fitting procedure for P10 and P10‐IrO 2 are shown in Figure 5c, d. Species 0 and 1 both have characteristic features of the singlet excitonic state. Given this observation, along with the identical time that species 1 takes to form in the presence and absence of IrO 2 , it can be assigned to a singlet excitonic state, which likely forms following vibrational relaxation of the initially formed hot state (species 0) in‐line with a recent time‐resolved Raman study of P10 which showed vibrational cooling occurs within 10 ps and that polaron formation can occur from both the vibrationally hot and thermalized exciton [53] . The SAS of species 2 (P10) has a maximum at ca.…”
Section: Resultssupporting
confidence: 67%
“…tion, along with the identical time that species 1 takes to form in the presence and absence of IrO 2 , it can be assigned to a singlet excitonic state, which likely forms following vibrational relaxation of the initially formed hot state (species 0) in-line with a recent time-resolved Raman study of P10 which showed vibrational cooling occurs within 10 ps that polaron formation can occur from both the vibrationally hot and thermalized exciton. [53] The SAS of species 2 (P10) has a maximum at ca. 635 nm which agrees with the previously reported polaron pair and electron polaron spectra of P10.…”
Section: Entrymentioning
confidence: 99%
“…The latter assignment is supported by spectroelectrochemical measurements of an FS5 film under negative applied bias (Figure S64) and is consistent with previous measurements on sulfone-containing polymers, ,, as well as with measurements on polyfluorenes. It has previously been shown that CT states and polarons can have similar absorption spectra. , The data in Figure d suggest that FS5 can transfer excitonic holes to TEA, with a substantial population of electrons being formed from 5 ps. Reductive quenching by TEA has been shown to occur on the picosecond timescale in several other studies. ,, By contrast, FS1 has no rise in amplitude at >5 ps, indicating that it does not generate electron polarons in detectable quantities on the picosecond timescale. This is consistent with the results from the previous section, which suggest that FS5 has a driving force for TEA oxidation while FS1 does not.…”
Section: Resultsmentioning
confidence: 88%
“…Reductive quenching by TEA has been shown to occur on the picosecond timescale in several other studies. 29 , 60 , 63 By contrast, FS1 has no rise in amplitude at >5 ps, indicating that it does not generate electron polarons in detectable quantities on the picosecond timescale. This is consistent with the results from the previous section, which suggest that FS5 has a driving force for TEA oxidation while FS1 does not.…”
Section: Resultsmentioning
confidence: 97%
“…As a result of the typically large exciton binding energy in organic materials, 33 excitons, or at least excitons generated with light absorbed near the absorption onset of a material and hence with little excess energy, do not spontaneously dissociate to free electrons and holes in particles/lms of conjugated polymers. Transient absorption spectroscopy has been used to conrm the presence of electrons/electron polarons in polymeric photocatalysts under sacricial operating conditions, 7,11,34 suggesting that the exciton drives the transfer of an electron between the sacricial electron donor (SED) and the polymer, oxidizing the SED in the process, and that the electron transferred to the polymer subsequently drives the reduction of protons. Previously, we used computational chemistry to explore a potential photocatalytic cycle for hydrogen evolution using poly(p-phenylene) as a prototypical linear conjugated photocatalyst and triethylamine (TEA) as the SED.…”
Section: Introductionmentioning
confidence: 99%